A Cumulative Effect by Multiple-Gene Knockout Strategy Leads to a Significant Increase in the Production of Sophorolipids in Starmerella Bombicola CGMCC 1576 - Liu, Jun; Zhang, Xinyu; Liu, Guodong; Zhao, Guoqin; Fang, Xiaoran; Song, Xin (Frontiers in Bioengineering and Biotechnology, 2022)
Sophorolipids (SLs), an important biosurfactant produced by S. bombicola, were one of the most potential substitutes for chemical surfactants. Few reports on the transcriptional regulation of SLs synthesis and the engineered strains with high-yield SLs were available. In this study, a Rim9-like protein (Rlp) and three transcription factors (ztf1, leu3, gcl) were mined and analyzed, and a progressive enhancement of SLs production was achieved through cumulative knockouts of three genes. The sophorolipid production of ΔrlpΔleu3Δztf1 reached 97.44 g/L, increased by 50.51% than that of the wild-type strain. Compared with the wild-type strain, the flow of glucose to SLs synthesis pathways was increased, and the synthesis of branched-chain amino acids was reduced in ΔrlpΔleu3Δztf1. The amount of UDP-glucose, the substrate for two glycosyltransferases, also increased, and the expression level of the key genes sble and UGPase for SLs synthesis increased by 2.2 times, respectively. The multiple-gene knockout strategy was proved to be highly effective to construct the engineered strain with high-yield SLs production, and this strain can be better used for industrial fermentation and reduce production costs.